The Andean Migratory Statute and the limitations of regional regulatory convergence - Condoy-Celi, Cynthia (2024)
Introduction: This article identifies the process of construction of the Andean Migration Statute, with emphasis on the participation of non-governmental actors. The Andean Migration Statute is a regional policy that occurs with a long-term bottom-up diffusion process, where the government's intention of regional normative convergence and the need for a change in approach brought about by social actors come together. Objective: it shows the limitations of the regional convergence on migration management. Methodology: this is qualitative research and develops a case study on the configuration of the Andean Migration Statute. It is based on the official documents of the Andean Community and other specialized studies. The theoretical framework is the South America migration governance and the diffusion process of public policy. Conclusions: the Andean Migration Statute incorporated a focus on guaranteeing rights for Andean residents, aligned with global governance on orderly and safe migration. Although this neglects to resolve other regional migration problems such as irregular migration flows and emigration. It is necessary to discuss regional migration governance to refocus attention on unresolved common problems.